2019
DOI: 10.3390/toxins11120695
|View full text |Cite
|
Sign up to set email alerts
|

The Latoia consocia Caterpillar Induces Pain by Targeting Nociceptive Ion Channel TRPV1

Abstract: Accidental contact with caterpillar bristles causes local symptoms such as severe pain, intense heat, edema, erythema, and pruritus. However, there is little functional evidence to indicate a potential mechanism. In this study, we analyzed the biological characteristics of the crude venom from the larval stage of Latoia consocia living in South-West China. Intraplantar injection of the venom into the hind paws of mice induced severe acute pain behaviors in wild type (WT) mice; the responses were much reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Different from other venomous insects, the larvae of a caterpillar lack a specialized venom gland [45]. Instead, venom is synthesized by secretory epithelial cells and stored inside the hollow canal of the setae [43]. The harpoon-shaped setae/spines have chitin-rich tips that easily break and thus serve as an injection needle for the venom.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different from other venomous insects, the larvae of a caterpillar lack a specialized venom gland [45]. Instead, venom is synthesized by secretory epithelial cells and stored inside the hollow canal of the setae [43]. The harpoon-shaped setae/spines have chitin-rich tips that easily break and thus serve as an injection needle for the venom.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…It seems that not only the KKS mechanism may be involved. Both genetic and electrophysiological studies with whole-cell patch clamp have, in fact, shown that transient receptor potential vanilloid 1 channel (TRPV1) is one of the primary targets of the L. consocia venom ( Figure 5) [43].…”
Section: Painmentioning
confidence: 99%
See 2 more Smart Citations
“…The fractions with contractile activity were pooled and further purified by a C 8 RP-HPLC (XBridge TM , C8, 5 µm, 25 × 0.46 cm, Waters, Milford, MA, USA). Elution was performed under solution A (water, 0.1% trifluoroacetic acid, v/v) and solution B (acetonitrile, 0.1% trifluoroacetic acid, v/v) with a linear solution B gradient of 0-100% as described previously [29]. During the elution, the absorbance value of the eluate was monitored at 215 nm/280 nm.…”
Section: Peptide Purificationmentioning
confidence: 99%